Role of T cells in the adjuvant effect of Bacillus firmus on the immune system of mice: intranasal and intratracheal immunization study with ovalbumin - Mlcková, P; Cechová, D; Marusková, L; Chalupná, P; Novotná, O; Prokesová, L (Folia microbiologica, 2003)
Functions of T cells were determined after intranasal and intratracheal immunization of mice with ovalbumin (Ova) and Bacillus firmus (Bf), a Gram-positive nonpathogenic bacterium of the external environment, or delipidated Bf (dBf) as adjuvants, with the aim to elucidate the mechanism of support of Ova-specific antibody production caused by Bf that had been observed in an identical experiment. Neither Bf nor dBf in a mixture with Ova stimulated Ova-specific T-cell response tested as antigen-specific blast transformation. By contrast, a mild polyclonal stimulation was observed in splenocytes from mice given dBf. In vitro incubation of splenocytes with 100 micrograms (but not 10 micrograms) of Bf or dBf led to a highly significant inhibition of proliferation below the control level in all groups of animals. Supernatants of splenocyte cultures were further tested for cytokine production. IL-10 and IFN-gamma were released after in vitro challenge with dBf and in some cases also with Bf. Analysis of sera demonstrated that administration of Ova + adjuvant brought about an increase in anti-Ova IgG1, IgG2a and IgG2b whereas treatment with Ova alone caused a rise in IgG1 only. The role of Bf or dBf in the enhancement of antigen-specific antibody production could be in influencing macrophages and inducing cytokine milieu composed of IL-10, IFN-gamma and other factors that leads to a bystander stimulation of specifically activated Ova-B cell receptor (Ova-BCR)-bearing cells.
Keywords: Administration, Intranasal; T-Lymphocytes; ovalbumin; Mice, Inbred BALB C; Ovalbumin; imunoglobulin G; Bacillus; cytokiny; T-lymfocyty; Mice; Cytokines; aplikace intranazální; Immunoglobulin G; aktivace lymfocytů; ženské pohlaví; Immunization; zvířata; Lymphocyte Activation; myši inbrední BALB C; myši; adjuvancia imunologická; Adjuvants, Immunologic; imunizace; Female; Animals